Climate change mitigation and the cost of equity: evidence from Malaysia - Brahmana, Rayenda Khresna; Hui, Wei You; Mohd Waliuddin, Mohd Razali (Inderscience Enterprises Ltd., 2015)
This study examines the effect of Climate Change Mitigation (CCM) on the cost of equity covering 266 Malaysian public listed companies from the period between 2010 and 2014. We find that CCM has a significant effect on the cost of equity. There are corporate attributes such as a firm's size, leverage, growth and risk effect on the cost of equity. However, only the leverage and risk are significant to the cost of equity. Interestingly, our research also discovered the unexpected direction for the relationship between CCM and the cost of equity, which is a positive relationship. This implies that the higher disclosure of CCM increases the cost of equity for the firms. In short, firms have to exchange to compromise between a lower cost of equity or a better environment. This research carries important findings for the policy makers. Policy makers may find that there is a trade-off between choosing to act responsibly towards the environment and achieving an optimum profit.